2014
DOI: 10.5137/1019-5149.jtn.9101-13.1
|View full text |Cite
|
Sign up to set email alerts
|

Normal pressure hydrocephalus versus atrophic dilatation to distinguish and predict the benefits of surgical intervention with a phase-contrast MRI technique

Abstract: AIM:To compare mean cerebrospinal fluid (CSF) volume in the aqueduct by using phase-contrast magnetic resonance imaging for the patients with idiopathic normal pressure hydrocephalus (INPH) and atrophic dilation (AD) to investigate the efficacy of this technique in predicting surgery. MATERIAL and METHODS:The MR images of a total of 80 individuals, consisting of 30 patients considered to have INPH, 20 patients with AD not proportional with cerebral sulci, and 30 control cases without a hydrocephalus clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Although no macroscopic obstruction is discernible on diagnostic imaging [ 4 , 17 ] some iNPH patients display elevated CSF outflow resistance [ 12 , 18 , 19 ] suggesting impaired CSF clearance and absorption. On the other hand, the CSF flow in iNPH patients appears hyperdynamic as demonstrated by an increased aqueductal CSF flow [ 20 24 ]. This hyperdynamic CSF flow may originate from a decreased intracranial compliance [ 13 , 25 29 ] but could alternatively be explained by CSF hypersecretion, a potential mechanism generally neglected in the pathogenesis of hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…Although no macroscopic obstruction is discernible on diagnostic imaging [ 4 , 17 ] some iNPH patients display elevated CSF outflow resistance [ 12 , 18 , 19 ] suggesting impaired CSF clearance and absorption. On the other hand, the CSF flow in iNPH patients appears hyperdynamic as demonstrated by an increased aqueductal CSF flow [ 20 24 ]. This hyperdynamic CSF flow may originate from a decreased intracranial compliance [ 13 , 25 29 ] but could alternatively be explained by CSF hypersecretion, a potential mechanism generally neglected in the pathogenesis of hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…A great degree of variation has been found in CSF flow parameters depending on the study: the upper limit of the flow rate ranges from 18 to 24 ml/min [ 2 , 3 , 11 ], and the upper limit of peak flow velocity from 9 to 10 cm/s [ 24 , 25 ]. Hence, the raw CSF flow values seem not to be a reliable and strong diagnostic criteria for hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are various PC MRI studies that have shown that the CSF flow in iNPH patients is in a hyper-dynamic state, which is in accordance with our results. Specifically, it has been shown that mean CSF flow is greater in iNPH but not AD patients compared to healthy controls [ 7 , 10 ], CSF motion increases in iNPH patients [ 16 ], and stroke volume increases in iNPH patients [ 9 , 17 , 18 ]. However, it is not currently possible to use markers such as stroke volume [ 8 ] to distinguish between iNPH and AD.…”
Section: Discussionmentioning
confidence: 99%
“…CSF motion in elderly groups has only been investigated in a small number of studies and there is no consensus on the characteristics of CSF motion in AD patients [ 3 , 7 , 8 ]. In the iNPH study, CSF motion appears to be hyper dynamic [ 3 , 9 , 10 ]. The aim of this study was to compare the CSF dynamics of healthy elderly volunteers with those of AD and iNPH patients.…”
Section: Introductionmentioning
confidence: 99%